Stability of Iceland type berm breakwaters - Sveinbjornsson, P.I. Pétur (TU Delft, 2013)
The goals of the project are the following: a) Design rules for the transaction of stone classes with depth have not yet evolved and the main goal of this project was to develop a stability criterion for the stones in that area (Primary goal). b) Stones on berm. Since the total amount of the largest stones (Class I) is usually limited, the combination of the amount of large stones on the berm and down the berm is important (Secondary goal). c) Recession. Recession will be measured in each test and thereby a large database on the subject will be made available for further research on the subject (Secondary goal). d) The location of the transition of the original and the reshaped profiles as the berm height changes as well as for different stone setups. This is also closely related to the primary goal of the project (Secondary goal). Numbers of model tests were performed in order to reach those goals.